2020
DOI: 10.3390/plants9010055
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Crassulacean Acid Metabolism (CAM) Photosynthesis in Cotyledons of the C4 Species, Portulaca grandiflora (Portulacaceae)

Abstract: Portulaca grandiflora simultaneously utilizes both the C4 and Crassulacean acid metabolism (CAM) photosynthetic pathways. Our goal was to determine whether CAM developed and was functional simultaneously with the C4 pathway in cotyledons of P. grandiflora. We studied during development whether CAM would be induced with water stress by monitoring the enzyme activity, leaf structure, JO2 (rate of O2 evolution calculated by fluorescence analysis), and the changes in titratable acidity of 10 and 25 days old cotyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Daily measurement of gas exchanges could have confirmed the evidence of both CAM and CAM-idling status in P. afra plants in response to prolonged water stress. However, even if we could not measure the gas exchanges, our hypothesis is supported by the recent work of Guralnick et al [ 22 ], which demonstrated the development of CAM activity through the titratable acidity levels and diurnal acid fluctuations. The daily acid fluctuation measured in the present study is in agreement with values found by Guralnick and Ting [ 20 ] in P. afra plants exposed to prolonged water stress.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Daily measurement of gas exchanges could have confirmed the evidence of both CAM and CAM-idling status in P. afra plants in response to prolonged water stress. However, even if we could not measure the gas exchanges, our hypothesis is supported by the recent work of Guralnick et al [ 22 ], which demonstrated the development of CAM activity through the titratable acidity levels and diurnal acid fluctuations. The daily acid fluctuation measured in the present study is in agreement with values found by Guralnick and Ting [ 20 ] in P. afra plants exposed to prolonged water stress.…”
Section: Discussionsupporting
confidence: 74%
“…As we observed a reduction in nocturnal organic acid (likely malic acid) accumulation with the progression of water stress, we supposed that photorespiration could be active during the CAM-idling status, contributing to keep oxidized the photosynthetic electron transport chain. The photorespiration could also provide CO 2 for the C3 metabolism during the daylight, as recently proposed by Guralnick and colleagues [ 22 ] for the C4 plant Portulaca grandiflora .…”
Section: Discussionmentioning
confidence: 77%
“…Above that, δ 2 H ne values in CAM plants may indicate if a facultative CAM plant performs C 3 or C 4 photosynthesis in the absence of water stress (Guralnick, Gilbert, Denio, & Antico, 2020 ; Winter, Garcia, & Holtum, 2008 ). The higher the contribution of C 3 or C 4 photosynthesis to a CAM plant's total carbon dioxide fixation, the more depleted are the δ 2 H ne values of cellulose and NSC (Luo & Sternberg, 1991 ; Sternberg, Deniro, & Johnson, 1984 ), thus indicating the absence of water stress.…”
Section: Resultsmentioning
confidence: 99%
“…P. grandiflora has been reported as salt tolerant and as an accumulator of proline [53]. Recently, in addition to the C4 photosynthesis common in the genus Portulaca, the pathway CAM was found in cotyledons of this species [54]. According to our knowledge, there are no studies regarding the salt tolerance of P. halimoides, except our previous reports on germination and early seedling growth in P. oleracea, P. grandiflora and P. halimoides [55] which revealed a greater resilience to drought of the latter, and a seemingly better response to salinity in P. grandiflora.…”
Section: Discussionmentioning
confidence: 99%